Sistem Replikasi Basis Data berdasarkan MySQL menggunakan Container Docker - Sholihah, Ilmiyatus; Darujati, Cahyo (Jurnal Teknologi Elektro; Vol 21 No 2 (2022): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2022.v21i02.P08, 2022)
This study aims to implement database replication using the master-slave technique. The main focus of this research is to run data replication on the master server so that it can be copied automatically on the slave server. Master-slave replication techniques aim to prevent data loss from system failure events or device damage on the main server. The concept of master-slave replication is to copy data from the master server database to the slave server so that users do not need to manually backup data from the database. Master-slave database replication is one of the features provided by the MySQL database application in the Docker container. Still, to run the replication system, some adjustments and configurations are required for the database application to establish a replication infrastructure automatically. In this study, the replication was run on a MySQL database application with 20 multimedia data files capacity of 100MB. Testing is done by entering data into the database on the master server. The test scenario in this study was to upload data and delete data. The test results show that the data changes automatically: the data on the slave server is the same as on the master server, even though the data on the master server has gone through data uploads and deletions. And vice versa, data changes made on the master server are also directly replicated on the slave server.